Minimal periodontal basic care - no surgery, no antibiotics, low adherence: what can be expected? : A retrospective data analysis - Bartha, Valentin; Mohr, Judith; Krumm, Boris; Herz, Marco M.; Wolff, Diana; Petsos, Hari (Quintessence international, 2022)
Objective: This retrospective study aimed to evaluate tooth loss and the evolution of periodontal inflammatory parameters within a strict nonsurgically treated patient cohort with < 2 supportive periodontal care visits per year, defined as minimal periodontal basic care, of 2.5 to 10.7 years. Method and materials: Data for nonsurgically treated patients were checked for: complete periodontal examination data at baseline (T0), after active periodontal therapy (T1), and after >= 2.5 years of supportive periodontal care (T2); smoking, diabetes mellitus, age (at least 18 years), plaque and gingival indices, bleeding on probing, percentage of residual pockets, supportive periodontal care adherence, and number of supportive periodontal care visits were assessed as risk factors for tooth loss. Results: In total, 132 patients were included (76 female, mean age 56.7 +/- 10.3 years), mean T-1-T-2: 4.5 +/- 1.6 years. 26.5% of all patients lost 118 teeth (0.5 teeth/patient, 0.12 teeth/patient/year). Plaque and bleeding parameters were: mean plaque control record, 59.77 +/- 28.07%; mean Papilla Bleeding Index, 47.46 +/- 34.12%; mean bleeding on probing, 33.46 +/- 21.52%. Supportive periodontal care duration (P = .013) and T-2 bleeding on probing (P = .048) were identified as patient-related risk factors for tooth loss. Conclusion: Minimal periodontal basic care was characterized by elevated bleeding on probing, Papilla Bleeding Index, and plaque control record scores. This possibly highlights a lack of consequent applied surgical intervention (if needed) transitioning into regular supportive periodontal care, including insufficient patient behavioral changes regarding domestic oral hygiene procedures and possibly nonaddressed proinflammatory dietary habits as a negative effect. An apparently low tooth loss rate could be observed. The duration of supportive periodontal care was identified as a risk factor for tooth loss.
Gesehen am 20.02.2023